Dilema Moral: Kepalsuan dan Keteladanan Komunikasi Politik di Indonesia - Muhammad E. Fuady (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
Political activities often generate political question toward ethics or moral issues. Political world believed as moral costly and degrading political figures into somewhat vague and manipulative person in order to maintain his/her positions. The case of Amien Rais, who failed to be Indonesian president resulted from fair election, supported such assumptions. Porn-video-streaming involving important political members also provided a strong case that political domain is actually a dirty world. But, in every situation, democracy needs a fair and honest people to give a high standard performance in politics. A good political leader would leave good memories and excellent example for other political leaders who fill in the same positions in the future.